Asthma and COVID-19 among healthcare workers from a mexican hospital: is there an association? - Jaime Morales-Romero; Patricia Paredes-Casillas; José E. López-Contreras; Kevin J. Arellano-Arteaga; Martín Bedolla-Barajas (Permanyer, 2022)
Background: Asthma does not appear to be a risk factor for developing COVID-19. Objective: The objective of the study was to analyze the role of asthma as a factor associated with COVID-19 among healthcare workers (HW). Methods: A crosssectional study was conducted in HW from a Mexican hospital. Data were obtained through an epidemiological survey that included age, sex, and history of COVID-19. Multivariate logistic regression analysis was performed to identify factors associated with COVID-19. Results: In total, 2295 HW were included (63.1% women; mean age 39.1 years); and 1550 (67.5%) were medical personnel. The prevalence of asthma in HW with COVID-19 was 8.3%; for the group without COVID-19, the prevalence was 5.3% (p = 0.011). The multivariate analyses suggested that asthma was associated with COVID-19 (OR 1.59, p = 0.007). Conclusion: Our study suggests that asthma could be a factor associated with COVID-19 in HW.